2015
DOI: 10.1111/wbm.12072
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy and the active metabolites of the endophytic fungus, AlternariaJ46, from Platycladus orientalis

Abstract: The endophytic fungus, Alternaria J46, was isolated from the stem of the medicinal plant, Platycladus orientalis. A suspension of Alternaria J46 mycelial segments and the culture filtrates of the fungi exhibited marked seed germination inhibition against the monocot wheat, large crabgrass, bromegrass, rice and barnyardgrass and weak inhibition against the dicot redroot pigweed and morning glory, but it was safe for use on soybean, rape, cucumber, tomato, lettuce and radish crops. It is possible to use J46 cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…In a pot trial tenuazonic acid exhibited an EC 50 between 119 and 795 μg/mL against 14 weeds but did not have any toxicity or damage to cotton ( Gossypium hirsutum ), Tobacco ( Nicotianatabacum ) and Asian Copperleaf ( Acalyphaaustralis ), even at a concentration of 1000 μg/mL. The field trial of tenuazonic acid controlled the two weeds, Amaranthusretroflexus and Digitariasanguinalis without affecting the Cotton (Hao et al 2015 ). Alternariol-9-methyl ether (1) which was isolated from endophytic Alternaria sp.…”
Section: Agrochemically Active Metabolitesmentioning
confidence: 94%
“…In a pot trial tenuazonic acid exhibited an EC 50 between 119 and 795 μg/mL against 14 weeds but did not have any toxicity or damage to cotton ( Gossypium hirsutum ), Tobacco ( Nicotianatabacum ) and Asian Copperleaf ( Acalyphaaustralis ), even at a concentration of 1000 μg/mL. The field trial of tenuazonic acid controlled the two weeds, Amaranthusretroflexus and Digitariasanguinalis without affecting the Cotton (Hao et al 2015 ). Alternariol-9-methyl ether (1) which was isolated from endophytic Alternaria sp.…”
Section: Agrochemically Active Metabolitesmentioning
confidence: 94%
“…Os resultados demonstram que M. yucatanensis, assim como outras espécies de Muscodor, produzem compostos voláteis em condições in vitro tóxicas para outros microrganismos e raízes de plantas. 43 Hao et al 57 estudaram o efeito aleloquímico do fungo endofítico Alternaria J46 frente a dezenove diferentes espécies vegetais, o fungo inibiu fortemente a germinação das monocotiledôneas testadas, e não mostrou inibição às dicotiledôneas, exceto a glória da manhã e bedros. Entretanto, houve alta inibição das culturas de trigo e arroz, o que impossibilita o uso deste fungo no campo.…”
Section: Aleloquímicos Produzidos Por Endófitosunclassified
“…Entretanto, houve alta inibição das culturas de trigo e arroz, o que impossibilita o uso deste fungo no campo. 57 Estudos demostram que os COVs produzidos por fungos também podem atuar com efeito aleloquímico de promoção de crescimento, como é o caso do endófito F. oxysporum (MSA 35) que promoveu o crescimento de alface (Lactuca sativa). O composto volátil β-cariofileno (Tabela 2) foi considerado um dos responsáveis pela promoção do crescimento da planta.…”
Section: Aleloquímicos Produzidos Por Endófitosunclassified
“…A suspension of Alternaria J46 mycelial segments and culture filtrates of the fungi display marked seed germination inhibition against different species, including the most important cereal crops worldwide for human consumption, wheat and rice. 14 This represents important economic losses as well as health problems due to Alternaria, which is also an important allergenic fungi and opportunistic human pathogen in immunocompromised patients. Previous studies carried out by our research team showed significant antifungal effects of commercial oregano and thyme essential oils against phytopathogenic fungi.…”
Section: ■ Introductionmentioning
confidence: 99%